How do people use Frankfurt Mainkai riverfront during a road closure experiment? A snapshot of public space usage during the coronavirus lockdown in May 2020 - Pandit, Lakshya; Fauggier, Gladys Vasquez; Gu, Lanqing; Knöll, Martin (Cities & health, 2021)
In a one-year long experiment, the City of Frankfurt has limited the vehicular access to an 800 m stretch of its Mainkai riverfront as part of its plans to improve quality of life and support green mobility. With pre-intervention data collected in July 2019, this article presents the first results on how pedestrians, cyclists and other user-groups have been using this open public space in May 2020, i.e. post road closure and during the coronavirus restrictions. Based on pedestrian counts and behavioural observations, the authors report on a changed pedestrian mobility, spatial distribution and different stationary activities such as playing, sitting and socializing. The results show an increased peak hour frequency among cyclists (+45%) and pedestrians (+20%) on Mainkai street, along with more vulnerable user groups including including children cycling independently (+1150%) and people with restricted mobility (+25%). The study underlines related initiatives world-wide that pedestrianization acts as a catalyst for safer and healthier urban environments. Particularly, under the impression of an ongoing coronavirus pandemic, the study suggests that (temporary) road closure to cars is a key element in qualifying public space that attracts different user-groups and caters to an increased need to become physically active and engage socially while keeping distancing rules.